Exploring Teacher's Effective Strategies in Catch-Up Fridays in Addressing Reading Gap - Rominimbang, Amer M.; Rominimbang, Noraifa S.; Barrera, Kenneth Ian B. (Randwick International of Education and Linguistics Science Journal, 2024)
The Covid-19 pandemic made a lot troubles in the educational field particularly in the area of reading proficiency. In response to this problem, the Department of Education in the Philippines implemented the Catch-up Fridays initiative which is dedicated to intensive remediation on selected areas. In this study, reading remediation is the focus. The study aimed to evaluate the effectiveness of various teacher strategies used in the sessions. Using a descriptive qualitative research approach, data were collected through semi-structured interviews with 13 purposively sampled teachers. The findings highlight the use of Philippine Informal Reading Inventory as key assessment tool and preference for strategies such as peer tutoring, and content-based instruction. However, challenges such as time constraints, insufficient resources, and lack of structured curriculum were identified. Despite the challenges posed by the situation, teachers demonstrated commitment on the program and in enhancing student outcomes. The study concludes that while Catchup Fridays show potential in addressing reading problems, its success hinges on adequate support such as resources and improved guidelines. The findings underscore the need for continuous improvement and support to optimize the program’s impact on reading proficiency.